(untitled) (Annals of Medical Research, 2021)
Aim: Colonoscopy is the established standard method for the evaluation of the colon. It has been reported that diabetes was associated with poor bowel cleansing and colorectal cancer in some studies. We aimed to evaluate the bowel preparation quality of type 2 diabetic and non-diabetic patients.Material and Methods: I62 diabetic and 65 non-diabetic patients were enrolled in this study and colon preparation quality was evaluated for each segment of colon (right, transverse and left) and total score was obtained according to Boston Bowel Preparation scale.Results: The successful bowel preparation rates were 64.5% in the diabetics and 75.4% in the non-diabetics, which wasn’t statistically significant. Cecal intubation rate was 80.6% in the diabetics, 90.8% in the non-diabetics and mean cecal intubation time was 7.78 min in diabetics, 8.9 min in non-diabetics. There were no significant differences in terms of cecal intubation time, cecal intubation rate and polyp detection rates between groups. We also found that bowel cleansing of right colon and transverse colon in the non-diabetics was superior to diabetics. Conclusion: Diabetes isn’t a negative factor for detection of colonic polyps and isn’t associated with inadequate bowel cleansing, but it associated with poor bowel cleansing in right and transverse colon, so physicians must be further careful for the possibility of obscure lesions of right and transverse colon in diabetic patients.